IMPROVING SELF-EFFICACY THROUGH FAMILY CENTER EMPOWERMENT MODEL: A QUASI-EXPERIMENT STUDY - Oktarina, Yosi; Nurhusna, Nurhusna; Mekeama, Luri; Aryani, Tuti; Subandi, Andi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Health problems in patients with coronary heart disease will have an impact on the patient's functional and psychological status. It will affect the quality of life of coronary heart disease patients. Self-efficacy is known to have a role in improving patient quality of life. Therefore, it is essential to increase self-efficacy in coronary heart disease patients. This research aims to determine the effect of the family-center empowerment model on the self-efficacy of coronary heart disease patients. This research uses a quasi-experimental design. The sample in this study was 50 patients with coronary heart disease in the cardiac polyclinic at Raden Mattaher Regional Hospital who were divided into two groups, namely 25 intervention groups and 25 control groups. The sampling technique used was consecutive sampling. The instruments used were questionnaires on respondent characteristics and cardiac self-efficacy. The family center empowerment model intervention consists of four sessions over four weeks. Data analysis used a paired t-test. And independent t-test. Before the FCEM intervention, the results showed no difference in mean self-efficacy in the two groups (p=0.56). However, after the FCEM intervention in the experimental group, self-efficacy increased significantly (p 0.01). Also, there is a difference in mean self-efficacy in the two groups (p = 0.003). This study shows an increase in self-efficacy after the FCEM intervention. It is hoped that nurses can apply FCEM interventions in the field of nursing clinical practice.